Isolation and Identification of Biosurfactant Producing Bacteria from Contact Pond Ponds of Palm Oil Industry Wwtp - Elma Damayanti Br Sembiring; M. Hasbi M. Hasbi; Budijono Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Biosurfactants are surfactant compounds produced by microorganisms, and have the ability to reduce surface tension, and can break oil. This study aims to obtain biosurfactant producing bacteria from the pond contact ponds of the palm oil industry WWTP in PT. Sawit Asahan Indah, Ujung Batu, Rokan Hulu Regency. This research was conducted in March-May 2019. First, samples were enriched and diluted with BHI media for 24 hours. Then bacteria are identified by biochemical methods and 18S rDNA. The results revealed that the total number of colonies was 8.7 x 106 Cfu / ml. Morphological and biochemical characteristics obtained 3 types of bacteria, namely Proteus vulgaris, Proteus mirabillis, and Escherichia coli. Two of them are biosurfactant bacteria with the Proteus vulgaris emulsification index 58.3%, and Proteus mirabillis 61.6%. Keywords: Biosurfactant, Proteus vulgaris, Proteus mirabilis, Emulsification Index, 18S rDNA, Biodegradation